Fabrication, bio-corrosion behavior and mechanical properties of a Mg/HA/MgO nanocomposite for biomedical applications. (25th December 2015) - Khalajabadi, Shahrouz Zamani; Abdul Kadir, Mohammed Rafiq; Izman, Sudin; Ebrahimi-Kahrizsangi, Reza
Abstract: The Mg/HA/MgO nanocomposites were fabricated with pure magnesium and the addition of different amounts of hydroxyapatite and periclase nanopowders using a blend-cold press-sinter powder metallurgy technique to improve the bio-corrosion and mechanical properties of the resulting material. Potentiodynamic polarization, immersion and mechanical tests were used to investigate bio-corrosion and mechanical properties of the nanocomposites produced. The compositions of the corrosion products and surface morphologies of the corroded specimens were characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, transmission electron microscopy, and field-emission scanning electron microscopy. The corrosion resistance of the nanocomposites is shown to increase from 0.25 kΩ cm 2 to 1.23 kΩ cm 2 with the addition of 10 wt.% MgO; additionally, decreasing the amount of HA from 27.5 to 12.5 wt.% is shown to yield an increase in the compressive failure strain from 4.2 to 11.5%. The corrosion products of the composite surface are shown to be primarily Mg(OH)2, HA and Ca3 (PO4 )2 . During immersion in SBF solution, the growth of the Mg(OH)2 nanorods on the nanocomposites increased the contact angle between the SBF solution and the substrate; as a result, the corrosion rate and hydrogen evolution rate decreased. The cell culture results indicate that Mg/HA/MgO nanocomposite is biocompatible with osteoblasts. Graphical abstract: Highlights: The lowest corrosion rate and hydrogen evolution rate were measured for Mg/12.5HA/10MgO (wt.%) nanocomposite. The Mg(OH)2 nanorods were synthesized on the Mg/HA/MgO nanocomposites during immersion in SBF solution. The compressive failure strain of Mg/HA/MgO nanocomposites increased as wt.% HA decreased. Osteoblast cells were observed to adhere on the surface of Mg/HA/MgO nanocomposites.